Pertumbuhan Generatif dan Komponen Hasil Generasi M-1 Padi Gogo (Oryza sativa L.) Varietas Lokal Kabupaten Pelalawan dengan Perlakuan Mutagen Sodium Azida (SA) - Nurhidayah, Tengku; Ali, Muhammad; Pratama, Javieri (Jurnal Agro Teknologi Tropika, 2016)
A research has been conducted to study the effect of the concentration of mutagen SA and obtain the best concentration to improve generative growth and yield components of M-1 generation on two local varieties upland rice from Pelalawan Regency. The research has been conducted at UPT Kebun Percobaan, Agriculture Faculty, University of Riau, from April to July 2014. The research used factorial experiment arranged in a Randomized Block Design (RBD). The treatments consisted of two local varieties upland rice from Pelalawan Regency (Korea and Lombo Sawah) and five concentrations of Sodium Azide (SA) (0,0 mM, 0,5 mM, 1,0 mM, 1,5 mM, 2,0 mM). Each treatment was replicated four times. Data were analyzed statistically with Analysis of Variance and the means were tested with Duncans New Multiple Range Test (DNMRT) at 5% level. Parameters observed were days to maturity, number of grains per panicle, filled grains percentage per panicle, filled grains weight per panicle and filled grains weight per clump. The result indicated that SA affected on increase number of grains per panicle and decrease filled grains percentage per panicle and filled grains weight per panicle. SA at concentration of 1,00 mM gave a better effect, which caused an increase in number of grains per panicle and filled grains weights per clump at two local varieties of Pelalawan upland rice at M-1 generation.